Engaging learner support: An investigation of faculty-library collaboration to provide live course-specific learner support within the online classroom environment - Alison Fields (Journal of Open, Flexible and Distance Learning, 2014)
Collaboration between faculty and learner support can create platforms for delivering seamless services for e-learners. Providing access to learning materials and activities with collocated tailored learner support creates an environment where e-learners are able to easily access everything needed for an enhanced, supported and more focussed learning experience. The emerging practice of embedding live librarians within online tertiary classrooms provides a new avenue for such learner support, and forms a natural extension of the library links and resources which are routinely found in online campuses, library websites and some online course pages. Embedded librarians can actively direct students to tailored library resources and tutorials and assist students directly, often in a library discussion forum, with their specific information and referencing questions. This paper reports on research in progress into the nature and effectiveness of using embedded librarians within online classrooms in New Zealand. It takes a multi-faceted view of this emerging practice, investigating the experience of students, faculty and the embedded librarians within the online classroom setting, and also considers how the library forum discussions operate and evolve over a trimester and what value they may have to the students in that class. Embedded librarians have been appearing in a small but growing number of online classrooms around the globe for the past decade, and in New Zealand are still the exception rather than the rule. Best practice has not yet been standardised globally and in the New Zealand environment has not yet been identified. There is opportunity to maximise the benefits of this new form of e-learner support and avoid potential pitfalls to enhance the learners’ experience and achievement by increasing engagement with relevant and pertinent information resources to support their learning.